2020
DOI: 10.1016/j.cellsig.2020.109807
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of nutrient uptake by AMP-activated protein kinase

Abstract: AMP-activated protein kinase (AMPK) is the downstream component of a protein kinase cascade that is a key regulator of energy balance at both the cellular and whole-body level. AMPK acts to stimulate ATP production and reduce ATP consumption when cellular ATP levels fall, thereby normalizing energy balance.Given the central role of AMPK in cellular carbohydrate and lipid metabolism, AMPK activation has been proposed to be a therapeutic target for conditions associated with dysfunctional nutrient metabolism inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 290 publications
(334 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, AMPK plays a central role in balancing cellular energy metabolism in obesity and other metabolic-related diseases. 77,78 Recent studies have shown that AMPK could increase the expression of SIRT3. 79,80 Therefore, we explored the association between SIRT3 and…”
Section: Sirt3 Was Involved In the Regulatory Mechanism Of Cur In Hep...mentioning
confidence: 99%
“…Furthermore, AMPK plays a central role in balancing cellular energy metabolism in obesity and other metabolic-related diseases. 77,78 Recent studies have shown that AMPK could increase the expression of SIRT3. 79,80 Therefore, we explored the association between SIRT3 and…”
Section: Sirt3 Was Involved In the Regulatory Mechanism Of Cur In Hep...mentioning
confidence: 99%
“…Under specific conditions, such as long fasting, the heart resorts to alternative energy producing substrates, including lactate, ketone bodies, and amino acids, especially branched-chain amino acids (BCAA). Cardiomyocytes are thus equipped with a whole range of substrate-specific membrane transporters, the expression of which is modulated according to the cardiac environment [ 26 , 27 ]. As the heart exhibits a low storage ability, they allow the constant entry of these substrates to supply the energy machinery.…”
Section: The Heart: An Oxidative Tissuementioning
confidence: 99%
“…According to Zhao and Saltiel, activating AMPK in the liver inhibits de novo lipogenesis, promoting fatty acid oxidation (β -oxidation). Furthermore, AMPK activation prevents hepatic steatosis by inhibiting the production of free fatty acids from adipose tissue (Figure 4) [ [37]. Li et al results suggest that AMPK may be used as a clinical therapy for the treatment of cholestatic liver damage.…”
Section: A Review Of Functions Of Protein Kinasesmentioning
confidence: 99%